Implementasi Kurikulum Jaringan Sekolah Islam Terpadu di Sekolah Menengah Pertama Islam Terpadu - Robingatin, Siti (Program Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
Islamic School Network Integrated Curriculum (JSIT) is a curriculum that integrate curriculum with the curriculum of the National Local Content that based on Islamic education, which includes the National curriculum, the curriculum of Islamic education, Scouting curriculum, and skilled curriculum. Purpose of this study is describing the implementation of the curriculum of Islamic Schools Network Integrated (JSIT) in Junior High School Islam Daarussalaam North Sangatta East Kutai realized in school programs and find the factors supporting and hindering the implementation of the curriculum of Islamic Schools Network Integrated Integrated Islamic (JSIT) in Islamic Integrated Junior High School Daarussalaam North SangattaÂ East Kutai. Research design of this study is a qualitative research. The main data sources obtained through interviews, observation, and documentation. And data analysis technique obtained from data reduction, data presentation and verification of data by performing triagulasi data. The results of this study that the implementation of the curriculum of Islamic Schools Integrated Network Islamic in Integrated Junior High School (SMPIT) Daarussalaam North Sangatta East Kutai showed the indications on the Internalization of Islamic values in all subjects, local content and program curriculum. Some factors Supported implementation of curriculum Islamic Integrated School Network ISAM (JSIT) are the role of parents both morally and materially. National Education affair minister monitored and evaluated as well as the social environment that religious and strategic place while inhibiting factor Human Resources who lack an understanding of the Integrated Islami Curriculum School (JSIT) and inadequate infrastructure.